PENGARUH INSEKTISIDA ABAMEKTIN DAN TANAMAN PERANGKAP TERHADAP HAMA PENGOROK DAUN (Liriomyza sp.) BAWANG MERAH PALU - Muttakin, Muttakin; Shahabuddin, Shahabuddin; Wahid, Abd. (AGROTEKBIS, 2018)
Local shallot of Palu famousfor its fried onion product of Palu is one of the main commodities specific to central sulawesi. The purpose of this research was to determine the effects of Abamectin insecticide and trap plant on Liriomyza sp. pest in Lembah Palu shallot variety plantation. The research was conducted in Petobo subdistrict, South Paludistrict and lasted from October 2016 to January 2017. This research used a randomized block design (RBD) consisting of four treatment; trap crop and abamectin, trap crop,abamectin, and control. The observed variables were leafminer species, imago population and the intensity of the pest attact on the shallot. The research obtained tree species of Liriomyza:L. chinensis, L.huidobrensis and L. sativae.The most effectivetreatment in controlling the Liriomyza sp.attacks was the combination of trap crop and abamectin insecticideswhichcould reduce the leafminersattackby up to 19.5%.